Find the sum of all positive integers c such that for some prime a and a positive integer b , a b + b a = c a .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
This is a fairly complicated but nice solution, also avoiding the use of the Fermat's Last Theorem. Checking all the details will likely make you a better mathematician.
Other correct solutions used the "Lifting the Exponent Lemma": for an odd prime p , if p does not divide b and c , then the order of p in b p − c p is the order of p in b − c plus one. This can be easily proven using the binomial coefficients, as in this featured proof. For generalizations and discussions, see http://www.artofproblemsolving.com/Resources/Papers/LTE.pdf
The most common kind of mistakes in this problem was not providing sufficient justification, sometimes to the point of dismissing cases by pure hand-waving.
D a m n !
We will solve the equation a b + b a = c a with the given conditions.
Firstly, we consider the case a ≥ 3 , a is a odd prime. Since a b + b a = c a , or equivalently, a b = c a − b a , we obtain b ≡ c ( m o d a ) .
If b ≡ c ≡ 0 ( m o d a ) , by using Lifting the Exponent Lemma, we have : v a ( c a − b a ) = v a ( a ) + v a ( c − b ) , which is equivalent to v a ( c − b ) = b − 1 . Since c a − b a = ( c − b ) ⋅ i = 0 ∑ a − 1 c i b a − 1 − i , we duduce that i = 0 ∑ a − 1 c i b a − 1 − i = a , which can not occur as i = 0 ∑ a − 1 c i b a − 1 − i > i = 0 ∑ a − 1 1 = a .
Now if b ⋮ a and c ⋮ a , put b = b 1 ⋅ a k ; c = c 1 ⋅ a l , l , k ≥ 1 ; a ∤ b 1 , a ∤ c 1 . If k > l , by dividing both side of the given equation by a l , we obtain a b − l a = c 1 a − b 1 a ⋅ a a ( k − l ) , then c 1 ⋮ a , contradict with the assumption a ∤ c 1 . Similarly, we deduce that k = l . Then we obtain the following equation : a b − k a = c 1 a − b 1 a . By similar arguments as above, we obtain a contradiction. Then we now have a "small conclusion" that a can not greater than 2 .
Now we consider the case that a = 2 . The given equation now can be rewritten as 2 b = ( c − b ) ( c + b ) . Put c + b = 2 m , c − b = 2 n , m > n ≥ 1 , m + n = b . If n = 1 , then c = b + 2 , we have 2 b + 2 = 2 m = 2 b − 1 , giving no solution. Hence, n > 1 . Therefore 2 b = 2 m − 2 n = 2 n ( 2 m − n − 1 ) ⋮ 4 , then b ⋮ 2 . Since 2 b = 2 m − 2 n , we deduce that 2 b > 2 2 b + 1 − 2 2 b − 1 = 3 ⋅ 2 2 b − 1 . Now we can give a bound for b : 2 ≤ b ≤ 6 . Then b ∈ { 2 , 4 , 6 } . By testing each case, we obtain the only solution : ( a , b , c ) = ( 2 , 6 , 1 0 ) . Therefore, the needed sum is equal to 1 0 .
Given that a is a prime and since a appears in the exponent twice and the base once so let's try moving the two terms to one side and leave the one term on the other side. We get a^b = c^a - b^a After factorizing, a^b = (c-b) (c^(a-1) + ... + b^(a-1)) therefore c-b divides a^b
so let c-b = a^q and (c^(a-1)+...+b^(a-1)) = a^r and q<=r consider q<=r, a^q<=a^r which implies that a^q|a^r now sub back in, c-b divides (c^(a-1)+...+b^(a-1))
Let us take mod c-b, So that expression becomes b^(a-1) + b^(a-1) + ... + b^(a-1) because c = b mod c-b if you count there are a terms in the sum, it becomes a b^(a-1) (mod c-b) but this term is 0 mod c-b because it is divisible by c-b so a b^(a-1) = 0 (mod c-b).
assume q >= 2 then b^(a-1) is divisible by a which implies b is divisible by a because a is prime and so now all the exponents are divisible by a and hence by quoting fermat's last theorem, we know that a has to be 2.
Hence, c^2 - b^2 = 2^b in fact c-b = 2^q and c+b = 2^r so b = (2^r - 2^q)/2 but b = q+r
We can force a contradiction out of this since the first expression is big and the second one is small. Therefore, there are no solutions except small ones, i.e. (2^r - 2^q)/2 is at least 2^(r-2) q+r is at most 2r so 2^r <= 8r so r<=5 which means b = q+r is at most 9.
We have to put in 9 values into the RHS of c^2=2^b+b^2 and check. Checking shows that (a,b,c) = (2,6,10) is a solution and since it is the only solution, sum of all possible c is 10.
We have known about the LTE technique that if x,y,n are positive integers and p is an odd prime, p is not a divisor of x and y but p is a divisor of x − y then v p ( x n − y n ) = v p ( a − b ) + v p ( n )
At first we get that c > b > 1 .
If a = 2 then 2 b = c 2 − b 2 . We infer that there exists 2 positive integers m,n such that m + n = b , c + b = 2 m , c − b = 2 n ( m > n ) . We can easily get m = 4 , n = 2 (Just prove that m < 6 ) so that ( a , b , c ) = ( 2 , 6 , 1 0 )
If a is not equal to 2, we have 2 case:
Case 1 : ( b , c ) = 1 . We infer that a is not a divisor of both b and c. So by using the LTE technique we will get v a ( c a − b a ) = v a ( c − b ) + 1 . Note that v a ( a b ) = b and v a ( c a − b a ) = v a ( a b ) so v a ( c − b ) = b − 1 → c − b = a b − 1 . But we have the inequality c a − b a > a ( c − b ) = a b which lead to a contradiction.
Case 2 : If b and c have common divisors we can infer that one of those divisors must be a. Take c = a h . t 1 , b = a k . t 2 ( a is not divisor of t 1 and t 2 ).
If h = k then t 1 a − t 2 a = a b − a h . Use the LTE and the inequality similarly to Case 1 again and it makes another contradiction.
if h < k then we get t 1 a − a a ( k − h ) . t 2 a = a b − a h .
We infer that b = a h ( because a is not divisor of t 1 ). But b = a k . t 2 > a h ( since k>h and b>1), again a contradiction.
At the end we conclude that there is only c = 1 0 that satisfies the equation.
a^(b-ma)=l^a-n^a=(l-n)(l^(a-1)+……+n^(a-1)), gcd of the two factors can only be 1 or a, so l-n=1 or l-n=a l-n=1 can not happen because l^a===l(mod a), n^a===n(mod a) if l-n=a and a is odd, then (l^(a-1)+……+n^(a-1))===a*n^(a-1) (mod a^2), which is not true so l-n=a=2 only solution is (a,b,c)=(2,6,10)
Generally, a rather sketchy solution. "So a < b also leads to another contradiction" in particular is unjustified, looks like wishful thinking.
Let p = a. Note that c - b divides c a − b a = p b , so c − b = p k . Making these substitutions, we have p b + b p = ( b + p k ) p . One notes that p must divide b, so we can let b = m p . Making this substitution and dividing by p p on each side, one notes m p + ( p m − 1 ) p = ( m + p k − 1 ) p . By Fermat's Last Theorem, p = 2 = a . Thus we are trying to solve 2 b + b 2 = c 2 . This implies 2 b = ( c + b ) ( c − b ) . Each of c + b and c − b must be powers of 2 . But by considering the difference between the two powers of 2 , one notes b < 1 1 . We can now simply test every b from 1 through 1 0 , and b = 6 is the only solution. This leads to c = 1 0 .
We first consider the case a = 2 . Then 2 b = ( c − b ) ( c + b ) . So both c − b and c + b are powers of 2 , with c − b being strictly smaller: c − b = 2 u , c + b = 2 u + v , where u and v are positive integers. This implies { 2 b = 2 u 2 u + v 2 b = 2 u + v − 2 u This system can be rewritten as { 2 u + v = b b = 2 u − 1 ( 2 v − 1 ) So we get 2 u + v = 2 u − 1 ( 2 v − 1 ) . If v ≥ 2 and u ≥ 4 , then 2 v − 1 > v ≥ 2 and 2 u − 1 ≥ 2 u ≥ 8 . One can see that in this case the product of 2 v − 1 and 2 u − 1 is strictly greater than the sum of v and 2 u , so this is impossible. If v = 1 , we get 2 u + 1 = 2 u − 1 , which by parity implies u = 1 , which does not work. If u = 1 , then 2 + v = 2 v − 1 , which has no solutions. If u = 2 , then 4 + v = 2 ( 2 v − 1 ) , which has one solution: v = 2 . This leads to ( a , b , c ) = ( 2 , 6 , 1 0 ) . Finally, if u = 3 , then 6 + v = 4 ( 2 v − 1 ) , which has no solutions.
Suppose now that a is an odd prime. By Fermat's theorem, b a ≡ b ( m o d a ) and c a ≡ c ( m o d a ) . Because c a − b a = a b ≡ 0 ( m o d a ) , we have c ≡ b ( m o d a ) .
Suppose c = b + a k e , where a and e are coprime. Then a b = ( b + a k e ) a − b a . Using the binomial formula, we get a b = a b a − 1 a k e + 2 a ( a − 1 ) b a − 2 a 2 k e 2 + . . . ≡ a k + 1 b a − 1 e ( m o d a k + 2 ) This implies that either b = k + 1 , or b ≡ 0 ( m o d a ) . If b = k + 1 , then a k + 1 = ( c − b ) ( c a − 1 + . . . + b a − 1 ) , so a k + 1 > ( c − b ) ⋅ a = a k + 1 e , a contradiction.
So, b must be divisible by a . Suppose b = a d . We can show that this is impossible in two different ways. The first way is to notice that a b + b a = c a can be rewritten as ( a d ) a + b a = c a , which for odd a has no solutions in positive integers by the Fermat's Last Theorem (proved by Andrew Wiles). The only problem with this argument is that it uses a very hard theorem, and there is a long-standing tradition in mathematics that strongly encourages the use of only those theorems for which you personally understand the proofs. So here is a different way to rule out this case, without using the "big guns".
The main idea is that the difference between two a -th powers cannot be too small. Recall that if b is divisible by a , then so is c . Suppose c = a f . Since ( a d ) a + ( a d ) a = ( a f ) a , we must have ( a d − 1 ) a + d a = f a . So d a ≥ ( a d − 1 + 1 ) a − ( a d − 1 ) a . By the binomial formula, this implies d a ≥ a ⋅ ( a d − 1 ) a − 1 . This implies d a > ( a d − 1 ) a / 2 , so d 2 > a d − 1 . If a ≥ 5 , this implies d 2 > 5 d − 1 , which is only true if d = 1 . If a = 3 , we get d = 1 , 2 , 3 , or 4 .
If d = 1 , for any a , then b = a and we have a a + a a = c a . So c a = 2 a a , which is impossible, because 2 is not an a -th power.
If a = 3 and d = 2 , then a b + b a is 3 6 + 6 3 = 3 3 ⋅ 3 5 , which is not a perfect cube. Similarly, a = 3 and d = 3 or d = 4 do not work.
As a result, the only solution to our equation is ( a , b , c ) = ( 2 , 6 , 1 0 ) , so the answer is 1 0 .
If a ≥ 3 , use the inequality, we can see that the equation can not be hold. If a = 2 , we have 2 b = ( c − b ) ( c + b ) and then we find out the unique solution of it is b = 6 , c = 1 0 . So the sum of all positive integers c satisfy the given equation is 10.
Problem Loading...
Note Loading...
Set Loading...
Conclusion .
The only solution is a = 2 , b = 6 , c = 1 0 , therefore the sum of all possible values of c is 1 0 .
Proof .
First we consider a special case: a = 2 . In this case,
2 b = c 2 − b 2 = ( c + b ) ( c − b )
Therefore c + b = 2 p , c − b = 2 q for some non-negative integers p , q such that p + q = b and q ≤ p − 1 . So, consider the following chain of inequalities:
2 ( 2 p − 1 ) ≥ 2 ( p + q ) = 2 b = 2 p − 2 q ≥ 2 p − 2 p − 1 = 2 p − 1 .
Then we get 2 p − 2 ≤ 2 p − 1 . One can check for p = 2 , 3 , 4 , 5 that this holds. For p ≥ 6 , notice that 2 x > x for any x , we have 2 p − 2 = 1 6 ⋅ 2 p − 6 ≥ 1 6 ( ( p − 6 ) + 1 ) > 2 ( p − 6 ) + 1 1 = 2 p − 1 .
Now we check the four cases of p . First, we rearrange 2 ( p + q ) = 2 p − 2 q as 2 q + 2 q = 2 p − 2 p . (Since 2 q + 2 q is strictly increasing, this allows us to check just a few small q 's.)
Therefore in this special case of a = 2 , the only possible case is c + b = 2 4 = 1 6 , c − b = 2 2 = 4 , which gives us b = 6 , c = 1 0 . It is easy to check that this is indeed a solution.
Now we assume that a is an odd prime (so a ≥ 3 ), and prove that in this case there is no solution at all. Suppose that b = a m b 1 , where m is a non-negative integer and b 1 is not divisible by a . So a b + a a m b 1 a = c a . Then, since b ≥ a m ≥ a m , we know that a a m divides a b , and thus divides c a . Therefore a m divides c . Suppose that c = a m c 1 , then we have a b = a a m c 1 a − a a m b 1 a a b − a m = c 1 a − b 1 a
If b = a m then b 1 a + 1 = c 1 a ≥ ( b 1 + 1 ) a > b 1 a + 1 , a contradiction. Therefore b > a m . So we know that a ∣ ( b 1 a − c 1 a ) . It is evident that c 1 > b 1 , so let d = c 1 − b 1 > 0 . By Fermat's Little Theorem one can prove that a ∣ d . Indeed, c 1 a ≡ c 1 , b 1 a ≡ b 1 ( m o d a ) , so d = c 1 − b 1 ≡ c 1 a − b 1 a ≡ 0 ( m o d a ) .
Before I proceed further, I'd like to mention a fact that is probably known by the reader: for any prime number n and integer 1 ≤ k ≤ n − 1 , the binomial coefficients C n k is divisible by n but not by n 2 . Actually this is readily seen in the formula C n k = k ! ( n − k ) ! n ! , where there is no factor n in the denominator, and there is exactly one n in the numerator.
Now, suppose that d = a t x , where t ≥ 1 is an integer, and that x is a positive integer not divisible by a . We have
a b = c 1 a − b 1 a = ( d + b 1 ) a − b 1 a = d a + C a 1 d a − 1 b 1 + ⋯ + C a a − 2 d 2 b 1 a − 2 + C a a − 1 d b 1 a − 1
The last term is equal to a t + 1 x b 1 a − 1 , so it is divisible by a t + 1 but not by a higher power of a . However, all of the first a terms d a , C a 1 d a − 1 b 1 , ⋯ , C a a − 2 d 2 b 1 a − 2 are divisible by a t + 2 .
Indeed, we have d a = a t a x a , where t a ≥ 3 t = t + 2 t ≥ t + 2 ; and for k = 1 ⋯ a − 2 , C a k d a − k b 1 k is divisible by a d a − k = a 1 + t ( a − k ) x a − k , where 1 + t ( a − k ) ≥ 1 + 2 t = t + 1 + t ≥ t + 2 .
Therefore, we get a b = a t + 2 y + a t + 1 z where y , z are integers such that y > 0 , and that z is not divisible by a . So a b = a t + 1 ( a y + z ) , which is a contradiction since a y + z is both > 1 and not divisible by a , thus cannot be a power of a . In conclusion, there is no solution when a is an odd prime.